IMPLEMENTASI_MODEL_PROBLEM_BASED_LEARNING DALAM _MENINGKATKAN KEAKTIFAN_SISWA MATA_PELAJARAN MATEMATIKA DI KELAS_IV SD NEGERI CEPOKO KOTA SEMARANG - Dwitya, Rahma; Ansori, Isa (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Abstract This study was used to determine the implementation of the Problem Based Learning model in mathematics subjects in class IV SD.Using descriptive qualitative methods.With research subjects all fourth grade students of SD Negeri Cepoko totaling 24 students.Data collection by interview, observation and documentation.Followed by data analysis, namely Data Collection, Data Reduction, Data Display and Conclusing Drawing / verification. At first students were not active during learning, after the teacher applied the Problem Based Learning method students became more active during learning. This study explains that the learning process using PBL must go through the stages of designing learning activities, implementing the PBL model and evaluating during the learning process in order to get the desired results.